Effectiveness of a group‐walking intervention for people with dementia based on quality of life and caregivers' burden - Myrta Kohler; Jeanette Mullis; Melanie Karrer; Juerg Schwarz; Susi Saxer (Wiley, 2021)
Abstract Aims To test the effectiveness of a 28‐week group‐walking intervention for person with dementia. Participants were accompanied by trained volunteers. The effectiveness was assessed according to the quality of life, ability to perform activities of daily living, independence, mobility, cognition, challenging behaviours and the burden on their caregiving relatives. Design Quasi‐experimental, one‐group, pretest-posttest trial. Methods Thirty‐two persons with dementia and their caregiving relatives were recruited. The nursing intervention consists on easy walking tours lasting three and a half hours. The walks were performed biweekly and each person with dementia had support from one or two trained volunteer helpers. Results The quality of life was stable through all seasons. The secondary outcomes were uneven. While the impairment (WHODAS) and the dependence (IADL) increased, the challenging behaviours and the burden on the caregivers were stable through all seasons.